Analysis of trace elements in multifloral Argentine honeys and their classification according to provenance - Pellerano, Roberto Gerardo (2012)
The concentrations of 14 trace elements Br, Ce, Co, Cr, Cs, Eu, Fe, La, Rb, Sb, Sc, Sm, Th and Zn) have been determined in 120 samples of light-coloured honeys from the provinces San Luis and La Pampa, middle Argentina, using instrumental neutronic activation analysis. The elemental composition was used in multivariate statistical analysis to discriminate the honeys according to geographical origin. Results indicated that element analysis provides a good prospect for discriminating honeys by regions, even if the element composition is not dependent on the year of harvest. Eight key variables (Ce, Cr, Cs, Fe, La, Sb, Sc and Zn) were identified by LDA as providing the maximum discrimination between samples according to their provenance. It was concluded that the methodology in its current state can be used to provide reliable origin information.